Governor Sir William Robinson and the Muar Succession: a consideration - Tham Junean,; Mohd Samsudin,; Suffian Mansor, (Penerbit UKM, 2023)
In 1877, the small territory of Muar in the Malay Peninsula was ceded to Maharaja (later Sultan) Abu Bakar of Johor after the death of Sultan Ali Iskandar Shah of Johor. This was done with the connivance and approval of the British Governor and Colonial Office, setting aside the claims of Sultan Ali’s son, Tunku Alam. Although presented locally as a triumph for the politicking of the Maharajah, the Muar Succession was a short-lived check to the British forward movement in the Malay Peninsula. This article attempts to explain the reason for this anomaly, and the role of Governor Robinson during the event. The qualitative research was conducted using primary sources like Arkib Negara Malaysia documents, colonial newspapers and Colonial Office files. Contrary to conventional historiography which portrays the British forward movement as linear and inevitable, we show that the personal initiative of the Governor of the Straits Settlements played a crucial role in the development of British policy towards Muar, which would later influence the politics of British colonial administration in the Malay Peninsula in the 19th century. In particular, the personal convictions of Governor Robinson against granting the Maharajah more influence marked the start of hardening colonial attitudes towards the Maharajah, leading to a resumption in British forward policy from the 1880s. The Muar affair would prove to be the exception that proves the rule, where the British experience in non-intervention in the Malay Peninsula provided instead justification for further direct expansion in the name of good administration.